PELAKSANAAN PELAYANAN PUBLIK DI DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI KOTA YOGYAKARTA DISAAT PANDEMI COVID 19 - Sediawati Sediawati; Ishviati J Koenthi (Kajian Hasil Penelitian Hukum, 2022)
Abstract: The paradigm of governance has undergone a shift from rule government to good governance, and from a centralized to decentralized system. Meanwhile, the implementation of a decentralized system has also caused a shift or transfer of management authority from the (central) government to local governments. In the context of good governance, public service is the main gate of government bureaucratic reform, because in public service it is a space where the government bureaucracy interacts directly with the community. In this new public service era, public services must be more responsive because they will be directly monitored in a transparent manner by the community. The implementation of public services before and after the Covid 19 pandemic and the performance of public service delivery at the Social Service, Manpower and Transmigration during the Covid 19 period. The results of the research obtained are that in meeting the community's needs for services, competent human resources (HR) are needed in providing services, and For changes in the form of services, all of which can be done offline, when the service is provided online, the service provider, in this case the Social Manpower and Transmigration Office, can make new standard operating procedures for services in online form, so that the needs of the community/citizens for services can be fulfilled. And even though public services are in online form, with a limited number of human resources, online services should also have a time limit for receiving services